2005
DOI: 10.1007/s11250-005-7049-y
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Milk Production in Udder Quarters with Subclinical Mastitis and Associated Economic Losses in Crossbred Dairy Cows in Ethiopia

Abstract: The objective of the study was to estimate the losses associated with subclinical mastitis (SCM) in crossbred dairy cows in the Central Highlands of Ethiopia. A split udder investigation was performed with 30 cows to determine production losses associated with SCM. Each quarter of the study cows was examined using the California Mastitis Test (CMT) and quarter milk production was measured over a period of 8 days. Production losses were determined for different CMT scores by comparing production of quarters wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
60
3
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(76 citation statements)
references
References 11 publications
12
60
3
1
Order By: Relevance
“…This study revealed significantly (P<0.05) higher prevalence of CPS as parity number increased. Similar findings were previously reported by (Oudessa Kerro and Fiseha Tareke, 2003;Mungube et al, 2005;Demelash Biffa et al, 2005;Kassaye Getahun et al, 2008;Mulugeta Yohannis and Wassie Molla, 2013). The age-multiparous-high prevalence relationship is explored to be due to decrease in teat patency, degree and frequency of previous exposure in multiparous old cows (Radostits et al, 2007).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…This study revealed significantly (P<0.05) higher prevalence of CPS as parity number increased. Similar findings were previously reported by (Oudessa Kerro and Fiseha Tareke, 2003;Mungube et al, 2005;Demelash Biffa et al, 2005;Kassaye Getahun et al, 2008;Mulugeta Yohannis and Wassie Molla, 2013). The age-multiparous-high prevalence relationship is explored to be due to decrease in teat patency, degree and frequency of previous exposure in multiparous old cows (Radostits et al, 2007).…”
Section: Discussionsupporting
confidence: 89%
“…SCM is 3 to 4 times more common than the clinical mastitis and it is not often detected by most of the dairy farmers; hence it is the major factor affecting the productivity of dairy cattle (Mungube et al, 2005). Reduction in milk production and quality, treatment cost, premature culling of cows and loss of genetic potential will follow leading to heavy economic losses (Leitner et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, quarter location, lnSCCpre and the interaction of parity with lnSCCpre and quarter location were significantly associated with lnSCCpost (El Bagir et al, 2010;Mungube et al, 2005).…”
Section: Discussionmentioning
confidence: 90%
“…This results in reduced milk quality and yield, which in turn leads to a reduction in the farmer's income as well as that of the dairy industry. This is mainly due to the prolonged diagnostics of the disease and long-term decrease in the milk yield and technological value (Mungube et al 2005; Halasa et al MIC mod = the MIC value most frequently occurred; MIC 50 = the MIC value for 50% isolates; MIC 90 = the MIC value for 90% isolates; S = susceptible isolates; I = intermediately resistant isolates; R = resistant isolates 2009). Moreover, unlike the clinical form of the disease, subclinical mastitis is widely spread among dairy herds (Gruet et al 2001).…”
Section: Discussionmentioning
confidence: 99%